Surabaya Generation Z Traffic Awareness: Strengthening Citizen Morals in Driving - Habibah, Siti Maizul; Sari, Beti Indah; Mohamad Razali , Marshelayanti (Universitas Negeri Surabaya, 2024)
One of the problems that are always faced in big cities is traffic problems. Thus, the national transportation system must develop its potential and role in realizing security, safety, order and smooth traffic. Legal awareness is needed from both law enforcement officials and the public, especially in this case traffic drivers. The problem in this paper is the problem of traffic awareness in the z generation of motorbikes. The research method uses descriptive quantitative, the population is students studying in Surabaya with a random sampling technique. Data collection uses a questionnaire through the Google form application and data analysis uses descriptive statistics. The results of the study show that the awareness indicators of generation Z motorists in traffic look very good.